The Strategies Used by Non-English Department Students in Acquiring Their Speaking Ability - Prastha, Alzar Putra; Devita Puji Puspitasari (Universitas PGRI Yogyakarta, 2025)
Speaking is an activity that everyone often does, especially in English. Speaking activities are never separated from them, such as making conversation, asking for help, suggesting, and the others. This study aimed to determine non- English students' strategies to acquire their speaking ability. The data collection method used qualitative methods, namely, collecting the open-ended questionnaire from Non-English Department students. The result shows that 68% of 114 respondents are not fluent in speaking English, and less than 6% are not capable of speaking English. It can be concluded that most respondents who can speak English are of elementary school age, and less than 3% are of kindergarten age. The difficulties usually encountered are pronouncing and speaking in English, which is about 32%, and less in 1% because they do not understand the word's meaning. Furthermore, the data shows that about 53% of students used entertainment to learn English, such as music, video games, etc. The trimmer is about 4% they are using an application to learn English. The dispelling myth of learning English is a typical justification for adopting a second language teaching strategy or approach based on first language acquisition that emerges from time to time. In addition, it can be concluded that the dispelling myth of learning English is still the same from time to time. Based on the research, mainly the students use repetition, imitation, natural order, no translation, and grammatical conceptualization in teaching.